2014
DOI: 10.1089/ars.2013.5259
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Hypertension: Role of the Kidney

Abstract: Significance: Renal oxidative stress can be a cause, a consequence, or more often a potentiating factor for hypertension. Increased reactive oxygen species (ROS) in the kidney have been reported in multiple models of hypertension and related to renal vasoconstriction and alterations of renal function. Nicotinamide adenine dinucleotide phosphate oxidase is the central source of ROS in the hypertensive kidney, but a defective antioxidant system also can contribute. Recent Advances: Superoxide has been identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
134
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(141 citation statements)
references
References 347 publications
(537 reference statements)
1
134
0
6
Order By: Relevance
“…We have found that elevated ROS production within the renal outer medulla of SS rats can be largely attributed to the multicomponent NADPH oxidases (Nox) (45) that catalyze the reduction of molecular oxygen to superoxide (O 2 ·Ϫ ) and H 2 O 2 . Among the seven different members of the Nox family of enzymes, Nox2 (also named gp91phox) and Nox4 are expressed in the kidneys of rats (3,5,18,21,22,30). Our data and findings of others indicate that Nox1 is expressed at very low levels in the medullary thick ascending limb of Henle (mTAL), and Nox5 has not been found in rodents (15,21,30).…”
mentioning
confidence: 46%
“…We have found that elevated ROS production within the renal outer medulla of SS rats can be largely attributed to the multicomponent NADPH oxidases (Nox) (45) that catalyze the reduction of molecular oxygen to superoxide (O 2 ·Ϫ ) and H 2 O 2 . Among the seven different members of the Nox family of enzymes, Nox2 (also named gp91phox) and Nox4 are expressed in the kidneys of rats (3,5,18,21,22,30). Our data and findings of others indicate that Nox1 is expressed at very low levels in the medullary thick ascending limb of Henle (mTAL), and Nox5 has not been found in rodents (15,21,30).…”
mentioning
confidence: 46%
“…For instance, dysregulation of antioxidants, particularly catalase and peroxidases, results in the accumulation of hydrogen peroxide, which can react with transition metals to subsequently form highly reactive and damaging species with reactivities, such as the hydroxyl radical. Furthermore, studies indicate the overproduction of superoxide, primarily by NADPH oxidase and mitochondria, and reduced superoxide metabolism by SOD and other antioxidants, can initiate or potentiate the development of hypertension (8). For example, it has been shown that during the onset of hypertension, patients have 7% lower antioxidant capacity, including decreased erythrocyte catalase content and enhanced oxidation of low-density lipoproteins (LDLs) (45, 266).…”
Section: Other Antioxidantsmentioning
confidence: 99%
“…As NADPH oxidase transfers electrons from NADPH, they react with oxygen to form superoxide, which is usually rapidly converted to hydrogen peroxide. All of the components necessary for NADPH oxidase to function are present in the kidney, including the presence of four different isoforms of this oxidase-NOX1, NOX2, NOX4, and NOX5 (8,33,112). The expression of these different NADPH oxidase isoform components has been observed throughout the cortex and medulla of the mammalian (including human) kidney, including in the mesangium (97,136,184,190), proximal convoluted tubules, distal convoluted tubules, collecting duct, macula densa (17,77,139,217,281,309,322), endothelium, and VSMCs (8).…”
Section: Nadph Oxidase Rosmentioning
confidence: 99%
“…These observations may help explain why there is an epidemiological association between high consumption of processed meat, which is typically high in fat, but not high red meat consumption, with coronary heart disease risk (Micha and others 2010) and hypertension (Lajous and others 2014). After all, renal oxidative stress has been suggested to contribute to hypertension by inducing renal vasoconstriction and renin release, among other mechanisms (Araujo and Wilcox 2014), and cardiac oxidative stress may lead to cardiac hypertrophy (Maulik and Kumar 2012). However, another study showed that L-carnitine, a compound abundantly present in beef, protected the heart and liver against oxidation in an atherosclerotic rat model (Dayanandan and others 2001).…”
Section: Insulin Resistancementioning
confidence: 99%